Ochrona konsumenta w razie niewypłacalności biura podróży - Szafran, Dominika (Koło Naukowe Doktryn Politycznych i Prawnych, Katedra Doktryn Politycznych i Prawnych, Wydział Prawa, Administracji i Ekonomii Uniwersytet Wrocławski, 2016)
The article concerns consumers protection in case of insolvency of travel agencies. The said problem is highly frequent and the existing ways of solving it are not always sufficient. This issue has been regulated by the European Union law and followed by the provisions of a directive being implemented in the Polish legal order. The legislator imposes on the entrepreneurs an obligation to have adequate safeguards in case of insolvency, which, unfortunately, is not often enough to cover the claims of clients. The article has presented what steps an injured consumer can take as well as what the possible solutions to such problems are
Keywords: niewypłacalność; odszkodowania; biura podróży; konsumenci